Self Determination Right Bagi Aceh: HAM Versus Integritas Wilayah Negara Kesatuan Republik Indonesia - sefriani sefriani (Fakultas Hukum Universitas Islam Indonesia, 2003)
Basically, GAM has the basic right demanding the manifestation of self determination for separating to Indonesia. It is based on the unjustice and suffering of Acehnese during the New Order Regime. However, some determination should be discussed intensively inresponding the Acehnese self determination, such as it must be considered the consequences and the ability of Acehnese on keeping their community survival and interaction to international community if the separation to Indonesia is permissible.